Real-World Use of Carvedilol in Children With Dilated Cardiomyopathy: Long-Term Effect on Survival and Ventricular Function - Adorisio, Rachele; Cantarutti, Nicoletta; Ciabattini, Marco; Amodeo, Antonio; Drago, Fabrizio (Frontiers in Pediatrics, 2022)
Background: Carvedilol is recommended for chronic heart failure (HF) treatment in children. However, the ideal dosage and way of administration of carvedilol is not standardized and data on its long term effects are lacking. The aim of this study was to assess the effect of a high dosage regimen of carvedilol on cardiac outcomes in children with dilated cardiomyopathy (DCM) and chronic HF. Methods: We conducted a retrospective cohort study, including all children affected by DCM and followed-up in Bambino Gesù children Hospital from 2003 to 2017. We analyzed medical records before starting treatment, at 1 year and at 3 years after reaching the maximum therapeutic dosage. Kaplan Meier analysis and Cox proportional hazard regression have been used to evaluate the effect of high dosage carvedilol therapy. The main outcome was a composite of all‐cause mortality and heart transplant. Results: Among the 286 children affected by DCM managed in our center, 65 were treated with a high dosage of carvedilol regimen (up to 1 mg/Kg/day). Heart rate reduction [mean reduction 30%, p<0.0001], ejection fraction improvement [ 32 +/- 9.4% vs 45.+/- 10.1%, p<0.0001] were statistically significant in those. These changes were particularly remarkable in patients under 6 years of age. Cox regression showed that the only independent predictor of long-term survival and freedom from heart transplant was the high dosage carvedilol therapy (p=0.00001). Conclusions: Treatment with high dosage of carvedilol, in addition to standard HF therapy, significantly improves ventricular function and survival in children with DCM and chronic HF